Exploring the compositional variability of magmas erupted at La Soufrière volcano, St Vincent, using chemo-stratigraphy and new 40Ar/39Ar ages - Beitris Morrison-Evans; Elena Melekhova; Richard Robertson; Brian Jicha; George Cooper; Holli Frey; Jonathan Blundy (Bulletin of Volcanology, 2026)
The compositional variation of individual volcanic centres over time is key to understanding magmatic processes in the underlying crust. La Soufrière volcano, St. Vincent, Lesser Antilles, has erupted predominantly basaltic andesite magmas for hundreds of thousands of years. Sampling of the recently re-exposed crater walls at La Soufrière reveals that sequentially emplaced crater lavas, feeder dykes and lavas on the volcano’s western flank are low-magnesium basaltic andesites with little variation in major and trace element concentrations. A single La Soufrière crater lava unit is more mafic (8 wt.% MgO, 51–52 wt.% SiO 2 ) and is compositionally similar to rare low-magnesium basaltic tephra from large explosive eruptions on St. Vincent, suggesting more primitive melts are present in the underlying crust but rarely reach the surface. New 40 Ar/ 39 Ar ages fill in a period of previously undocumented eruptive history and highlight an unconformity within the crater: a crater lava dated at 25.2 ± 3.8 ka is overlain by considerably younger lavas dated at 7.9 ± 7.7 and 5.7 ± 4.4 ka. A hornblende-gabbro xenolith is dated at 475.6 ± 28.3 ka, in agreement with early pre-Somma magmatism at La Soufrière volcano. Combining new and published data, we show that hiatuses in the geochronological record coincide with major summit collapse events and that the system appears to have stabilised compositionally after the most recent Somma collapse. The compositional uniformity of La Soufrière basaltic andesites is consistent with buffering of magma compositions by a crystal mush in the underlying crust. Commonly erupted plutonic xenoliths at St. Vincent likely represent fragments of such mushes.

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Analytical method interferences for perfluoropentanoic acid (PFPeA) and perfluorobutanoic acid (PFBA) in biological and environmental samples - Jacqueline Bangma; James McCord; Nathan Giffard; Kate Buckman; Jonathan Petali; Celia Chen; Daniel Amparo; Barbara Turpin; Glenn Morrison; Mark Strynar (Chemosphere, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Conventional versus drug-eluting embolic transarterial chemoembolization with doxorubicin: comparative drug delivery, pharmacokinetics, and treatment response in a rabbit VX2 tumor model - Ron C. Gaba; Ramzy C. Khabbaz; Ruth N. Muchiri; Joseph D. Morrison; Lobna Elkhadragy; William M. Totura; Jonathan P. Samuelson; Herbert E. Whiteley; Ryan L. Deaton; Peter L. Nguyen; Maria Sverdlov; Jeremy J. Johnson; et al. (Drug Delivery and Translational Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Infantile Onset of Spinocerebellar Ataxia Type 5 (SCA-5) in a 6 Month Old with Ataxic Cerebral Palsy - Gillian Rea; Sandya Tirupathi; Jonathan Williams; Penny Clouston; Patrick J. Morrison (The Cerebellum, 2020)
Spinocerebellar ataxia type 5 (SCA-5) is a predominantly slowly progressive adult onset ataxia. We describe a child with a presentation of ataxic cerebral palsy (CP) and developmental delay at 6 months of age. Genetic testing confirmed a c.812C>T p.(Thr271Ile) mutation within the SPTBN2 gene. Seven previous cases of infantile onset SCA-5 are reported in the literature, four of which had a CP presentation. Early onset of SCA-5 presents with ataxic CP and is a rare cause of cerebral palsy.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Biases in Model-Simulated Surface Energy Fluxes During the Indian Monsoon Onset Period - Tirthankar Chakraborty; Chandan Sarangi; Mithun Krishnan; Sachchida Nand Tripathi; Ross Morrison; Jonathan Evans (Boundary-Layer Meteorology, 2019)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

High connectivity in a long-lived high-Arctic seabird, the ivory gull Pagophila eburnea - Glenn Yannic; Jonathan M. Yearsley; Roberto Sermier; Christophe Dufresnes; Olivier Gilg; Adrian Aebischer; Maria V. Gavrilo; Hallvard Strøm; Mark L. Mallory; R. I. Guy Morrison; H. Grant Gilchrist; Thomas Broquet (Polar Biology, 2016)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Abundance and distribution of major groups of diazotrophic cyanobacteria and their potential contribution to N 2 fixation in the tropical Atlantic Ocean - Nicole L. Goebel; Kendra A. Turk; Katherine M. Achilles; Ryan Paerl; Ian Hewson; Amanda E. Morrison; Joseph P. Montoya; Christopher A. Edwards; Jonathan P. Zehr (Environmental Microbiology, 2010)
Summary The abundances of six N 2 ‐fixing cyanobacterial phylotypes were profiled at 22 stations across the tropical Atlantic Ocean during June 2006, and used to model the contribution of the diazotrophs to N 2 fixation. Diazotroph abundances were measured by targeting the nifH gene of Trichodesmium , unicellular groups A, B, C (UCYN‐A, UCYN‐B and UCYN‐C), and diatom‐cyanobiont symbioses Hemiaulus–Richelia , Rhizosolenia–Richelia and Chaetoceros–Calothrix . West to east gradients in temperature, salinity and nutrients [NO 3 ‐ + NO 2 ‐ , PO 4 3− , Si(OH) 4 ] showed the influence of the Amazon River plume and its effect on the distributions of the diazotrophs. Trichodesmium accounted for more than 93% of all nifH genes detected, dominated the warmer waters of the western Atlantic, and was the only diazotroph detected at the equatorial upwelling station. UCYN‐A was the next most abundant (> 5% of all nifH genes) and dominated the cooler waters of the eastern Atlantic near the Cape Verde Islands. UCYN‐C was found at a single depth (200 m) of high salinity and low temperature and nutrients, whereas UCYN‐B cells were widespread but in very low abundance (6.1 × 10 1 ± 4.6 × 10 2 gene copies l −1 ). The diatom‐cyanobionts were observed primarily in the western Atlantic within or near the high Si(OH) 4 input of the Amazon River plume. Overall, highest diazotroph abundances were observed at the surface and declined with depth, except for some subsurface peaks in Trichodesmium , UCYN‐B and UCYN‐A. Modelled contributions of Trichodesmium , UCYN‐B and UCYN‐A to total N 2 fixation suggested that Trichodesmium had the largest input, except for the potential of UCYN‐A at the Cape Verde Islands.

Spatial‐temporal variability in diazotroph assemblages in Chesapeake Bay using an oligonucleotide nifH microarray - Pia H. Moisander; Amanda E. Morrison; Bess B. Ward; Bethany D. Jenkins; Jonathan P. Zehr (Environmental Microbiology, 2007)
Summary The distribution of nitrogen‐fixing microorganisms in the Chesapeake Bay was investigated using fingerprints from a nifH microarray comprised of 706 60‐mer oligonucleotide nifH probes representing cultivated organisms and environmental clones from different nifH clusters. Diverse nifH targets, amplified from samples using degenerate nifH primers, were detected in water column and sediment samples collected in April and October, 2001–2002. Total nifH richness and diversity (Simpson's and Shannon indices) were highest at the most riverine, oligohaline North Bay station. In most samples, the highest diversity was in nifH Cluster 3, which includes many anaerobes, while Cluster 1 (α‐, β‐ γ‐ Proteobacteria, Cyanobacteria) targets had the greatest microarray signal intensities. In a multidimensional scaling analysis, deep water communities from April and October were similar within each of the sampling sites, while the surface communities had more variability. Diazotroph communities in the water column in the North Bay were distinct from the Mid‐ and South Bay communities, and there was a gradual change in sediment diazotroph assemblages from the North to the South Bay. Diazotrophic assemblages from the majority of the water column samples from the Mid‐ and South Bay clustered with the sediment assemblage in Mid‐Bay. Dissolved inorganic nitrogen, salinity, dissolved organic carbon and dissolved organic phosphorus had a significant relationship with the diazotrophic bacterioplankton community. Higher diversity in the freshwater end of the system may reflect variability in disturbance rates and environmental conditions such as forms and concentrations of organic matter, nutrients and oxygen.

Beyond Noah: Saving Species Is Not Enough - JONATHAN V. HIGGINS; TAYLOR H. RICKETTS; JEFFREY D. PARRISH; ERIC DINERSTEIN; GEORGE POWELL; SUZANNE PALMINTERI; JONATHAN M. HOEKSTRA; JOHN MORRISON; ADAM TOMASEK; JONATHAN ADAMS (Conservation Biology, 2004)

MUSCLE-DERIVED CD45−SCA-1+C-KIT− PROGENITOR CELLS GIVE RISE TO SKELETAL MUSCLE MYOTUBES IN VITRO - CASSANDRE L. ROYER; JONATHAN C. HOWELL; PAUL R. MORRISON; EDWARD F. SROUR; MERVIN C. YODER (In Vitro Cellular & Developmental Biology - Animal, 2002)